Hubungan Pola Asuh Orang Tua Permisif dengan Moral Tidak Baik Remaja dan Implikasinya terhadap Konseling Perorangan - Nurul Latifah; Evi Fitriyanti (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
The research objective was to determine the relathionship between permissive permissive parenting styles with bad moral behavior and the implications of individual counseling if there is a relathionship between permissive parenting styles with students bad moral behavior. The research method used is a correlational quantitative type with a survey approach. With a sampel size of 104 students. The questionnaire used is a likert scale wich contains 22 statement items for permissive parenting, and 11 statement for bad morals. Based on the result of the pearson product moment correlation test, the results are 0,555. The correlation coefficient was consulted with table r at a significance level of 5%, namely 0,1622. The correlation coefficient of 0,555 means that the level of strength of relationship (correlation) between the permissive parenting style variables with morally is not good, namely the moderate/adequate category. The correlation number is the results above is positive, namely 0,555, so the relationship between the two variables is unidirectional.the conclusion is that there is a significant and unidirectional relathionship between the permissive parenting style of the students with bad morals, which means that the higher the permissive parenting, the higher the bad morals of the students. The counseling teacher effectively implies individual counseling services to alleviate the bad moral problems of students at SMA PGRI 24 Jakarta.